PUBLIC-PRIVATE PARTNERSHIP PADA SISTEM PENYEDIAAN AIR MINUM (SPAM) SEMARANG BARAT - Saputra, Feri Lintang; Priyadi, Budi Puspo; Dwimawanti, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Partnership is part of governance to carry out governmental functions in fulfilling public service needs. Public-private partnership is one type of partnership that can be conducted by the government based on its partnership arena, namely the private sector as an institution outside of the government. SPAM Semarang Barat is an example of a successful public-private partnership project in Indonesia, as evidenced by the timely completion of construction and successful implementation of operations from water production, processing, to distribution to the community without encountering issues such as debt, or defaults. At its inauguration, SPAM Semarang Barat has successfully produced water and reached 62,4% of its capacity of 1,000 liters per second to later serve 7,000 household connections. This success is attributed to the coordination and good partnership between PDAM Tirta Moedal and PT. Air Semarang Barat. This research aims to analyze the implementation operational aspect of public-private partnership in SPAM Semarang Barat and to identify the driving factors for the success of SPAM West Semarang implementation. This research used a qualitative descriptive method with data collection through observation, interviews, and documentation techniques. The results showed that the public-private partnership in SPAM Semarang Barat has achieved success based on four partnership success principles consisting of transparency and commitment, partnership oversight, negotiation, and role equality carried out by both parties in the operation of SPAM West Semarang. The driving factors for the success of SPAM West Semarang implementation consist of good governance through central government support programs in capacity development and legal certainty